VD_FINDINFO Jug / 2015 / 40 vom 16. Februar 2015 - VD Tribunal cantonal (2015)
EFFETS ACCESSOIRES DU DIVORCE, PRÉVOYANCE PROFESSIONNELLE, CHOSE JUGÉE | 22 LFLP, 22a LFLP, 25a LFLP, 61 LTF, 7 OLP, 8a OLP, 315 al. 1 CPC (CH)